PENGARUH BUDAYA ORGANISASI, ORGANIZATIONAL CITIZENSHIP BEHAVIOR, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMP SWASTA SE-KECAMATAN PAGEDANGAN - Christina Endar Kumaladewi; Ersam Mahendrawan; Lili Nurlaili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of organizational culture, Organizational Citizenship Behavior (OCB), and work motivation on teacher performance at private junior high schools in Pagedangan District, Tangerang Regency. Teacher performance is one of the key factors in improving the quality of education. The research used a survey method with a causal associative research design. The population consisted of 108 teachers from private junior high schools in Pagedangan District. A saturated sampling technique was applied, in which the entire population was selected as the research sample. Data were collected using a Likert-scale questionnaire. Data analysis included descriptive and inferential statistical analyses. The prerequisite tests consisted of normality, homogeneity, multicollinearity, heteroscedasticity, and autocorrelation tests. Hypothesis testing was conducted using simple linear regression, multiple linear regression, t-test, F-test, and the coefficient of determination. The findings revealed that organizational culture had a positive and significant effect on teacher performance. Organizational Citizenship Behavior (OCB) also had a positive and significant effect on teacher performance. Work motivation was found to have a positive and significant effect on teacher performance. Simultaneously, organizational culture, OCB, and work motivation had a positive and significant effect on teacher performance. The coefficient of determination (R²) was 0.554, indicating that 55.4% of the variation in teacher performance could be explained by the three independent variables, while the remaining 44.6% was influenced by other factors beyond the scope of this study. Therefore, improving teacher performance should be achieved through strengthening organizational culture, fostering Organizational Citizenship Behavior (OCB), and enhancing teachers' work motivation in an integrated manner within the school environment.